2005
DOI: 10.1038/sj.jhh.1001824
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of the Gln223Arg polymorphism in the human leptin receptor gene, and traits related to obesity in Mexican adolescents

Abstract: Polymorphisms of leptin receptor (LEPR) may contribute to a common form of obesity and, as a consequence, obesity-related diseases. We evaluated the potential role of genetic variation at the LEPR gene in heart sympathetic activity and other traits related to obesity in Mexican adolescents. Adolescents aged between 12 and 17 years, with steady body weight for the last 3 months were included. We evaluated anthropometric measurements, blood pressure, seric glucose, insulin, leptin levels, heart sympathetic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
3
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 32 publications
6
59
3
4
Order By: Relevance
“…In literature, both alleles of these SNPs have been reported as risk alleles for type 2 diabetes and obesity, and a metaanalytic study reported nonsignificant associations. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]48 Consequently, additional studies in larger populations need to be carried out, to verify the involvement of these coding LEPR SNPs in the 'fetal insulin hypothesis'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, both alleles of these SNPs have been reported as risk alleles for type 2 diabetes and obesity, and a metaanalytic study reported nonsignificant associations. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]48 Consequently, additional studies in larger populations need to be carried out, to verify the involvement of these coding LEPR SNPs in the 'fetal insulin hypothesis'.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we therefore examined the effect of common SNPs in LEP and LEPR on birth weight and adult metabolic risk factors for type 2 diabetes measured in young twins recruited from the East Flanders Prospective Twin Survey (EFPTS). The SNPs studied have previously been associated with type 2 diabetesrelated traits in other populations, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and are either nonsynonymous or located in a region that might be of importance in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few investigations on the concurrent relationships between leptin-receptor polymorphisms, plasma leptin levels and sympathetic nerve activity (15). In the present study, three leptin-receptor polymorphisms (Lys109Arg in exon 4, Gln223Arg in exon 6, and Lys656Asn in exon 14) from buffy coats (white blood cells) that may contribute to obesity (11)(12)(13)(14) were studied in a Caucasian male population with a wide range of body mass indices (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…17 This could potentially lead to the development of new drugs that could target both hypertension and the metabolic syndrome. 18 Also, Guizar-Mendoza et al 19 performed a study to establish the relationship between Gln223Arg polymorphism in the human leptin receptor gene (LEPR) and traits related to obesity in Mexican adolescents. Their study showed that obese adolescents have higher heart sympathetic activity, blood pressure, insulin and leptin levels than non-obese subjects, and furthermore those who were carriers of the Gln223Arg polymorphism of LEPR have sympathetic overactivity and hypertension.…”
mentioning
confidence: 99%